PENGARUH PENAMBAHAN KONSENTRASI PUTIH TELUR TERHADAP TEKSTUR NUTRISI DAN SENSORI TAHU BAKSO - Suherman, Mela Oktora; Faizal, Muhammad (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama'ah, 2023)
This study aims to determine the effect of adding various concentrations of egg white on the texture, nutritional content, and sensory properties of tofu meatballs. The study was conducted using a completely randomized design (CRD) with six levels of egg white concentration (0%, 2%, 4%, 6%, 8%, and 10%) and three replications. The parameters observed included hardness (texture), protein content, and sensory scores (color, aroma, taste, texture, and overall acceptance). The results showed that increasing the concentration of egg white up to 6% significantly increased the hardness, protein content, and sensory scores of tofu meatballs. A concentration of 6% is the optimum point that produces the best quality product. Above this concentration, there is a decrease in texture and sensory quality. Therefore, the addition of 6% egg white is recommended for the formulation of tofu meatballs that are optimal physically, nutritionally, and sensorily.